2014
DOI: 10.1128/iai.02169-14
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Susceptibilities of Corneal Pseudomonas aeruginosa Clinical Isolates to Neutrophil Extracellular Trap-Mediated Immunity

Abstract: Ocular bacterial keratitis, often associated with Pseudomonas aeruginosa bacterial infection, commonly occurs in contact lens wearers and may lead to vision impairment. In this study, we analyzed the contribution of neutrophil extracellular traps (NETs) to the mediation of protection during ocular keratitis. Both invasive and cytotoxic P. aeruginosa clinical isolates induced NET release by neutrophils. NETs carried the characteristic histone proteins, elastase, lysozyme, myeloperoxidase, and metabolic enzymes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 39 publications
4
38
1
Order By: Relevance
“…The cell number and viability were evaluated by counting trypan blue dye impermeable and permeable cells. This purification procedure yielded 99% viable bone marrow-derived neutrophils with 90% purity as described in Siemsen et al 10 and Shan et al 16 Opsonophagocytic assay…”
Section: Neutrophil Isolationmentioning
confidence: 99%
“…The cell number and viability were evaluated by counting trypan blue dye impermeable and permeable cells. This purification procedure yielded 99% viable bone marrow-derived neutrophils with 90% purity as described in Siemsen et al 10 and Shan et al 16 Opsonophagocytic assay…”
Section: Neutrophil Isolationmentioning
confidence: 99%
“…They also contain granules and can release anti-microbial molecules similar to the resident granulocytes and can create “neutrophil extracellular traps” (NETs). NETs are networks of DNA-rich fibers embedded with histones and granule proteins including neutrophil elastase, cathepsin G and myeloperoxidase that can trap and kill bacteria and fungi extracellularly, without phagocytosis (40, 45, 93, 107). The monocytes can differentiate into macrophages when they enter the tissue and also phagocytose cells and debris.…”
Section: What Is Inflammation?mentioning
confidence: 99%
“…HL‐60 cell line, human promyelocytic leukemia cells, can be differentiated into granulocyte‐like cells using a wide variety of agents, such as all‐trans retinoic acid (ATRA), butyrate, hypoxanthine, dimethyl sulfoxide (DMSO) or dimethylformamide (DMF) . Differentiated HL‐60 cells (dHL‐60) have already been applied in studies deciphering mechanisms of NETs formation . It was reported that dHL‐60 cells were able to release NETs in response to a variety of stimuli, including both synthetic (ROS‐dependent phorbol 12‐myristate 13‐acetate (PMA) and ROS‐independent calcium ionophore (CI)) and physiological NETosis inducers ( C. albicans, S. flexneri, S. aureus and interleukin‐8).…”
Section: Introductionmentioning
confidence: 99%